A new basic creep model coupled with a thermomechanical model for the numerical simulation of the time-dependent behaviour of concrete structures - Valente, Tiago S. (2019)
This work is dedicated to the description of a new basic creep model that was developed and integrated in a thermo-mechanical model already available in a FEM-based software – FEMIX. The basic creep model is based on the Dirichlet series expansion of the Double Power Law (DPL) approach, and is capable of predicting the aging creep behaviour of cement based materials (CBM) since early ages. Based on experimental results, the model resorts to a non-linear least square datafitting operation to various loading ages creep compliance curves, and determines a set of model defining coefficients to simulate the aging viscoelastic properties of any CBM. This model was integrated with a thermo-mechanical model capable of simulating maturation, shrinkage and cracking phenomena of CBM. The good predictive performance of the implemented model is appraised by simulating experimental tests at material and structural scale.